Гемодинамічний ефект втручань непрямої реваскуляризуючої дії при лікуванні регматогенного відшарування сітківки - Завгородня, Наталія Григорівна; Дедов, А. В.; Івахненко, Олена Михайлівна; Zavhorodnya, N. G.; Dedov, A. V.; Ivakhnenko, O. M. (My University, 2014)
Introduction. Retinal detachment without treatment leads to irreversible blindness. Retinal tears often form at chorioretinal degeneration areas — regions where there is a decrease in local circulation. Indirect revascularization interventions allow to increase blood flow in the eye without the manipulation with eye tissues and maintaining the principle of antegrade blood flow in the ophthalmic artery. The aim was to determine the hemodynamic efficiency of indirect revascularization interventions in patients operated extrascleral methods for rhegmatogenous retinal detachment. Material and methods. The study involved 52 patients of the main group (operated extrascleral methods also performed ligation of the terminal branches of the external carotid artery) and 24 patients in the control group (myopia with lattice degeneration). Doppler and rheoophthalmography were performed — both studies with compression tests before and after the intervention. Results. Managed to significantly increase the volume (pulse blood volume 0.53 mm3, minute blood volume to 42.25 mm3) and speed (at 0,84–3,44 cm/s for different pools) characteristics of ocular blood flow. But most of the indicators are significantly lower than those in the control group, although the changes in intraocular pressure as a result of the treatment create difficulties to assess changes in volume characteristics. The question of functional efficiency of indirect revascularization interventions requires further study.
Hemodynamic effect of indirect revascularization interventions in the treatment of rhegmatogenous retinal detachment
Keywords: retinal detachment; ocular hemodynamics; indirect revascularization; extrascleral interventions; відшарування сітківки; реваскуляризація; гемодинамічний ефект